Portal Cavernoma Cholangiopathy Due To Extrahepatic Portal Vein and Supra-Mesenteric Vein Thromboses Associated with Congenital Protein C Deficiency in a Young Adult - Esumi, Shun; Morishita, Eriko; Yasuda, Mitsunori; Nakajima, Kanta; Imashuku, Shinsaku (Archives of Clinical and Medical Case Reports, 2019)
Idiopathic onset of portal vein thrombosis (PVT) and/or superior mesenteric vein thrombosis (SMVT) in young adults could be associated with congenital thrombophilia, resulting from mutations in the genes encoding antithrombin, protein C, or protein S. This report describes a 39-year-old man who developed symptoms of cholangitis and was incidentally found to have PVT and SMVT with cavernous transformation. The patient was found to have protein C deficiency (activity: 42–53%, antigen: 46%). Gene sequencing revealed a heterozygous mutation at exon 8 c.793C>T (p. Leu265Phe). The history of this patient suggested that thrombosis in his splanchnic venous system developed due to alcoholism plus congenital protein C deficiency. The patient has been managed with complete abstinence from alcohol and treatment with oral rivaroxaban.